2020
DOI: 10.1038/s41394-020-0261-1
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord injury in infancy: activity-based therapy impact on health, function, and quality of life in chronic injury

Abstract: Introduction Spinal cord injury (SCI) in infancy magnifies the complexity of a devastating diagnosis. Children injured so young have high incidences of scoliosis, hip dysplasia, and respiratory complications leading to poor health and outcomes. We report the medical history, progression of rehabilitation, usual care and activity-based therapy, and outcomes for a child injured in infancy. Activity-based therapy (ABT) aims to activate the neuromuscular system above and below the lesion through daily, task-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…The patient’s improved respiratory trajectory as well as gains in trunk control are similar to that of another child on whom we recently reported [ 10 ], though that patient had not required the use of chronic mechanical ventilation. The patient in this case report had never developed head control, and following intervention, he gained both head and upper thoracic trunk control.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The patient’s improved respiratory trajectory as well as gains in trunk control are similar to that of another child on whom we recently reported [ 10 ], though that patient had not required the use of chronic mechanical ventilation. The patient in this case report had never developed head control, and following intervention, he gained both head and upper thoracic trunk control.…”
Section: Discussionsupporting
confidence: 77%
“…Children with this constellation of insults are at high risk for needing chronic mechanical ventilation for many years, if not their entire life. We report the case of a two-year-old male with a history of prematurity at 29 weeks gestational age and with an early-onset severe cervical SCI complicated by prolonged mechanical ventilation whose respiratory status improved with intensive activity-based therapy (ABT) [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This association between postural control, gross motor function, and mobility as scored on the GMFM is consistent with observations in children with cerebral palsy (Butler et al, 2010) and gains in trunk control likely contributed to gains in GMFCS level. Recent studies show that children with SCIs who received 60 ABLT sessions or more showed improved trunk control based on Segmental Assessment of Trunk Control scores (Argetsinger et al, 2019, 2020; Behrman et al, 2019; Goode‐Roberts et al, 2021). Mechanisms for improved trunk control align with those activating the neuromuscular system below the lesion via sensory input during ABLT (Angeli et al, 2014; Rejc & Angeli, 2019), as well as potential activation of trunk musculature above, across, and below the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Broken line arrow indicates onset of sound stimulus. Scale bars = 500 ms. Bi, biceps brachii; MG, medial gastrocnemius; sound, recorded train blast; TA, tibialis anterior.showed improved trunk control based on Segmental Assessment of Trunk Control scores(Argetsinger et al, 2019(Argetsinger et al, , 2020Behrman et al, 2019;Goode-Roberts et al, 2021). Mechanisms for improved trunk control align with those activating the neuromuscular system below the lesion via sensory input during ABLT(Angeli et al, 2014;Rejc & Angeli, 2019), as well as potential activation of trunk musculature above, across, and below the lesion.…”
mentioning
confidence: 99%
“…Infancy is a rich period of sensorimotor experiences, typically learning through trial and error, that together with maturation and activity-dependent plasticity drive development ( Campos et al, 2000 ; Pape, 2012 ). Infants who have interruptions to development due to disease, illness, or injury, alter the malleable natural learning process, deviate from this well-known trajectory, and are at risk for maladaptive neuroplasticity ( Campos et al, 2000 ; Pape, 2012 ; Bhutta et al, 2017 ; Argetsinger et al, 2020 ). Spinal cord injury (SCI) presents unique challenges to the health and development of young children when injured under 5 years of age ( Schottler et al, 2012 ), and perhaps even more so when injured at birth.…”
Section: Introductionmentioning
confidence: 99%